Study of the factors influencing customer patronage to Spinelli Coffee Company. - Sng, Adrian Tiam Huat. (2008)
Recent years have seen the rapid proliferation of gourmet coffee chains in Singapore. In line with this trend, the team decided to conduct a study on factors that affluence consumer’s patronage to Spinelli Coffee Company, a typical gourmet coffee chain. Twelve choice factors were selected for testing. This was done after a review of literature on similar studies in the Food and Beverage industry.